The Ikhwani Sect in Chinese Islam: Historical Evolution, Reformist Ideology, and Sociopolitical Adaptation - Mousa, Mehad (MAQOLAT: Journal of Islamic Studies, 2025)
The Ikhwani sect represents one of the most influential reformist movements within Chinese Islam, emerging in the late nineteenth century under the leadership of Ma Wanfu (1849–1934). Inspired by Wahhabi ideas encountered during his studies in Mecca, Ma Wanfu sought to purify Chinese Islam by calling for a return to the Quran and Hadith while opposing syncretic practices such as Sufi saint veneration and Confucian-influenced rituals. This paper investigates the historical evolution, doctrinal foundations, and sociopolitical adaptation of the Ikhwani through three major phases: its ideological formation (1890s–1918), institutional consolidation under the Ma warlords (1918–1949), and pragmatic accommodation under Communist governance (post-1949). Drawing upon archival sources, mosque records, and key doctrinal texts, the study employs the theoretical frameworks of religious institutionalism and adaptive resistance to examine how the Ikhwani maintained theological integrity while surviving successive regime changes. The paper argues that the sect’s quietist orientation, pedagogical investment, and ritual standardisation provided a sustainable model of religious resilience. By comparing the Ikhwani to other reformist movements in the Islamic world, this study highlights the unique pathways through which Islam adapted to the Chinese sociopolitical context.